Prevalence of CYP2C19 alleles, pharmacokinetic and pharmacodynamic variation of clopidogrel and prasugrel in Bangladeshi population. (May 2015) - Bin Sayeed, Muhammad Shahdaat; Hasan Apu, Mohd Nazmul; Munir, Maliha Tabassum; Ahmed, Maizbha Uddin; Islam, Mohammad Safiqul; Haq, M Maksumul; Ahsan, Chowdhury H; Rashid, M A; Shin, Jae Gook; Hasnat, Abul
Summary: The extent to which cytochrome P450 (CYP) 2C19 genotype influences the effectiveness of clopidogrel remains uncertain due to considerable heterogeneity between studies. We used the polymerase chain reaction restriction fragment length polymorphism (PCR‐RFLP) method for genotyping loss of function (LOF) allele, CYP2C19*2 and gain of function (GOF) allele, CYP2C19*17 in 163 patients undergoing PCI and 165 healthy volunteers from an ethnically distinctive Bangladeshi population. Thirty‐eight patients took prasugrel and 125 patients took clopidogrel among whom 30 patients had their clopidogrel active metabolites (CAM) determined by LC‐MS/MS 1–1.5 h after clopidogrel intake. All patients who underwent PCI had their P2Y12 per cent inhibition (PRI) measured by VerifyNow System. The impact of different genotypes on CAM and PRI were also determined. We did not find significant variation of CYP2C19*2 ( P  > 0.05) and CYP2C9*17 ( P  > 0.05) alleles among healthy volunteers and patients. CAM concentration as well as PRI by clopidogrel varied significantly ( P <  0.05) based on genotypic variation of CYP2C19*2 and CYP2C19*17 individually. Such influence was not observed in case of prasugrel. Genotypic variation did not impact PRI but as a whole PRI by prasugrel was better than that of clopidogrel ( P <  0.05). Due to presence of both of alleles the effect on PRI by clopidogrel could not be predicted, effectively indicating possible involvement of other factors. Genotype guided clopidogrel dose adjustment would be beneficial and therefore we propose mandatory genotyping before clopidogrel dosing. Prasugrel proved to be less affected by genotypic variability, but due to lack of sufficient long‐term toxicity data, caution would be adopted before substituting clopidogrel.